Epidemiology of Open Fractures in a Nigerian Teaching Hospital - Nwagbara, Ifeanyi Charles; Nwabueze, Francis Chukwudi (Nigerian Journal of Orthopaedics and Trauma, 2019)
Background: The management of open fractures has been of great challenge to surgeons over the years, and these fractures are often associated with considerable patient morbidity and high socioeconomic consequences. Epidemiological studies are of great importance in the management of these conditions as the information obtained will be used to define priorities and enhance the understanding of this challenging subgroup of traumas. Objective: The aim of this study was to define the epidemiological profile of patients who were managed for open fractures of the long bones at a teaching hospital in South East Nigeria. Materials and Methods: This was a retrospective and descriptive epidemiological study involving open fractures of the long bones managed at a teaching hospital in the southeastern part of Nigeria over a period of 3 years, from January 2014 to December 2016. Data which were collected from patients’ case notes were subjected to descriptive analysis, and the results were presented with simple frequency tables, percentages and charts. Results: Seventy patients with 73 fractures were treated for open fractures within the period of the study. The male to female ratio was 4.3:1, and the peak age incidence was 20–29 years (30%). The most common cause of the injury was motor vehicle accidents (82.9%), of which 64.3% of cases were as a result of motorbike accidents. The leg bones were the most affected site (63%) while the Gustilo type III fractures were the most common injuries (67.1%). The average time interval from injury to presentation was 10 h. Wound infections were the most frequent complications observed, followed by delayed union. Conclusion: Open fractures are challenging conditions which affect mainly the young and active males in our society. The victims often present late which affects the management outcome. The burden of open fractures can be minimised in our society by efforts aimed at reducing the menace of motorbike operators, the latter being the most common cause of the injury.